INCREASING THE NUTRITIONAL VALUE AND EXPANDING THE RANGE OF SAUCES FOR HEALTH - Bashta Алла; Stetsenko Наталія; Bazhay-Zhezherun Світлана (Biota. Human. Technology, 2025)
The purpose of the study is to select a fruit and berry and spice flavouring composition with a high content of biologically active substances and to produce a health-promoting sauce from it. Methodology. Both traditional and non-traditional fruits and berries, spices and flavoured raw materials were investigated for the production of a health-promoting sauce. The content of biologically active substances in each type of raw material was determined using standard methods: pectin substances, bioflavonoids, ascorbic acid, carotenoids, dietary fibers, organic acids necessary to give health properties to the final product. A complex indicator based on qualimetric methods was used to quantitatively assess the quality of the finished sauces. Scientific novelty. According to the content of the main biologically active substances, according to the developed complex quality indicator, it is proposed to create a puree-mix composition for sauce with a combination of spicy-flavoured medicinal raw materials. This is done in order to increase the nutritional value of the product, give it health properties and create competitive products on the market. Conclusions. In this study, the feasibility of using a berry mixture based on blackcurrants and cherries and spicy and aromatic raw materials to produce a health-promoting sauce was investigated and confirmed. According to the research results, both blackcurrants and cherries contain a significant amount of pectin substances, bioflavonoids, carotenoids and vitamin C, which confirms the possibility of their use for the production of healthy food. According to the comprehensive quality indicator developed, the optimum ratio of blackcurrants to cherries in the finished sauce is 1.5:1. In order to additionally enrich the sauce with biologically active substances, give it pleasant organoleptic properties and expand the range of healthy sauces, blackcurrant leaf powder and hyssop powder were added as a spice and flavouring additive in an amount of 0.6 %.